Inflasi Pemoderasi ROA, EPS dan DER Terhadap Return Saham Perusahaan Consumer Goods di JII - Suandi Suandi; Ahmad Amir Aziz; Sanurdi Sanurdi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study aims to partially and simultaneously examine the effect of Return on Assets (ROA), Earning Per Share (EPS), and Debt Equity Ratio (DER) partially and simultaneously on stock returns in consumer goods companies listed on the Jakarta Islamic Index (JII) 2019- 2021. The method used is associative quantitative. Data analysis techniques using multiple regression and Moderated Regression Analysis (MRA). The tool used to test the data under study was the SPSS version 25 program. As for testing the influence of the moderating variable using the Macro Process 3.1 developed by Andrew F. Hayes, which has been integrated with SPSS version 25. The population in this study were all registered companies. On the Jakarta Islamic Index (JII), the sample is only companies engaged in the consumer goods sector. The company, namely PT. Unilever Indonesia, Tbk., PT. Kalbe Farma, Tbk., PT. Indofood Sukses Makmur, Tbk., and PT. Indofood CBP, Tbk. The study results show that ROA and EPS have no partial effect on stock returns. DER has a partial effect on stock returns. ROA, EPS, and DER affect stock returns. Inflation as a moderating variable cannot strengthen or weaken the effect of ROA and EPS on stock returns. The existence of inflation can strengthen the effect of DER on stock returns.